Orientalist Desires and Gothic Manifestations: A Study of William Beckford's 'Vathek' - Hamad, Fatimah Harbi; Mkhailef, Mishaal Harb (BATARA DIDI : English Language Journal, 2024)
This study offers a critical analysis of Gothic motifs and Orientalist themes in William Beckford’s Vathek with a view of how the latter contributes to the construction and reproduction of the ideological boundaries between the East and the West which are underpinned by cultural and moral differentialism. This way, the research illustrates how fear, horror and the supernatural are mobilised by Beckford to represent the Oriental as a space that is inherently dangerous and spiritually degenerate. The focus is also made on how the settings of the novel the confusing, infernal halls of Eblis, the vast, mysterious landscapes are not just the background, but characters themselves who embody and intensify the main character’s moral and spiritual degeneration. Furthermore, the penetration provided by the study gives insights as to how figures such as Nouronihar and Carathis exemplify yet disrupt the Orientalist stereotype of the fatal female. Due to this research, the interconnectivity between Gothic and Orientalist Studies has been presented, and it gives an insight into how socio-political imperialisms such as culture supremacy are perpetuated by Vathek. In other words, the findings enrich extant scholarly debate by offering an analytic of how the two architectonic styles weave together in the novel, to create cultural and moral ideologies.